Ubiquitously Occurring Perfluoroalkyl and Polyfluoroalkyl Substances: An Overview of Food and Environmental Contamination and Implications for Human Health - Jaglan, Poonam; Buttar, Harpal S; Wilson, Douglas; Telessy, Istvan G (Scripta Medica, 2026)
Perfluoroalkyl and polyfluoroalkyl substances (PFAS), commonly known as ‘forever chemicals’, are synthetic, anthropogenic compounds widely used in food packaging, processing equipment and nonstick surfaces. Their strong carbon–fluorine bonds make them highly persistent in the environment and within living organisms, including humans. This review focuses on the chemical structures of PFAS, their similarity to fatty acids, environmental contamination pathways, their entry into the food chain and water systems, their biological behaviour and their adverse health effects. Our observations suggest that the harmful effects of PFAS pollutants may be even more far-reaching, as they may jeopardise the function of the cardiorespiratory, neurological and reproductive systems in humans. PFAS analogues exhibit exceptionally long biological half-lives in humans with 2.7 to 5.1 years for perfluorooctanoic acid (PFOA), 3.4 to 5.7 years for perfluorooctane sulfonate (PFOS) and 2.8 to 8.5 years for perfluorohexane sulfonate (PFHxS), often persisting in blood and tissues for several years after exposure has ceased. This prolonged retention allows PFAS to accumulate over time, increasing the likelihood of chronic exposure and long-term health consequences even at low environmental concentrations. Evidence-based regulations by food and environmental regulatory agencies, along with projections of the impacts of regulatory intervention, are needed to protect public health.